Role of the lone star tick, Amblyomma americanum (L.), in human and animal diseases - Goddard, Jerome; Varela-Stokes, Andrea S. (Veterinary parasitology, 2009)
We reviewed scientific literature pertaining to known and putative disease agents associated with the lone star tick, Amblyomma americanum. Reports in the literature concerning the role of the lone star tick in the transmission of pathogens of human and animal diseases have sometimes been unclear and even contradictory. This overview has indicated that A. americanum is involved in the ecology of several disease agents of humans and other animals, and the role of this tick as a vector of these diseases ranges from incidental to significant. Probably the clearest relationship is that of Ehrlichia chaffeensis and A. americanum. Also, there is a definite association between A. americanum and tularemia, as well as between the lone star tick and Theileria cervi to white-tailed deer. Evidence of Babesia cervi (= odocoilei) being transmitted to deer by A. americanum is largely circumstantial at this time. The role of A. americanum in cases of southern tick-associated rash illness (STARI) is currently a subject of intensive investigations with important implications. The lone star tick has been historically reported to be a vector of Rocky Mountain spotted fever rickettsiae, but current opinions are to the contrary. Evidence incriminated A. americanum as the vector of Bullis fever in the 1940s, but the disease apparently has disappeared. Q fever virus has been found in unfed A. americanum, but the vector potential, if any, is poorly understood at this time. Typhus fever and toxoplasmosis have been studied in the lone star tick, and several non-pathogenic organisms have been recovered. Implications of these tick-disease relationships are discussed.